Religious pluralism and interreligious theology : the Gifford lectures---an extended edition - Schmidt-Leukel, Perry (Maryknoll, New York : Orbis Books, 2017)
Interreligious dialogue has encouraged many theologians in all major religious traditions to consider whether other religions may offer a different but nevertheless genuine and valid path of salvation or liberation. Perry Schmidt- Leukel, in this extended version of his 2015 Gifford Lectures, argues that this position--often called "religious pluralism"--must be developed within particular insights supplied by each of the major traditions. Although severe barriers to religious pluralism exist within each tradition, he shows nevertheless that possibilities for a pluralist understanding exist in Christianity, Judaism, Islam, Hinduism, Buddhism, and Chinese religions. Interreligious theology, he argues, carries the promise of being the theology of the future. (Publisher).
A fractal interpretation of religious diversity
Includes bibliographical references and index
Keywords: Religious -- Pluralism; Religious -- Relations; Dialogue -- Religious aspects